Pengaruh Store Atmosphere, Service Quality dan Promosi Terhadap Revisit Intention Konsumen pada Cafe Titik Terang Payakumbuh - Rahmiatul Ismi; Rah Utami Nugrahani (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Based on records from the Payakumbuh City Investment and One-Stop Integrated Service Office (DPMPTSP), the number of cafes in Payakumbuh City increased by 62.5% from 2020 to 2023, indicating a growing trend in the café business. However, Titik Terang Café, with its natural ambience concept, has faced a decline in repeat visit intentions in the past year. This study aims to determine the influence of store atmosphere, service quality, and promotion on customer revisit intentions at Kafe Titik Terang. This study used a sample of 385 respondents and collected data through a questionnaire method. Based on the results of research using descriptive analysis with the help of SPSS 21, it shows that store atmosphere, and promotion have a positive and significant effect partially on revisit intention. While service quality has no partial effect on revisit intention. This study suggests that Titik Terang maintain a cozy cafe atmosphere with attention to appropriate background music. Although service quality and promotion are very good, companies need to strengthen customer loyalty and increase revisit intention through periodic surveys and relevant promotional content.